DAKWAH ISLAM RAHMAT LI AL-ʻALAMIN HUSEIN JA’FAR AL-HADAR: KONSEP DAN PENGARUHNYA TERHADAP KEBERAGAMAAN KAUM MILENIAL DI MEDIA SOSIAL - Nur Mufidatul Ummah; Yoga Irama (JIA (Jurnal Ilmu Agama), 2021)
As a result of the many Islamic groups and groups who have different understandings of the meaning of rahmat li al-‘alamin, some of them have misunderstood the meaning. It is proven by the amount of propaganda on social media, acts of intolerance and violence that are based on the name of Islam are very contrary to the goal of Islam as a religion of mercy that creates peace and safety for the entire universe. So in this article, we review and examine the idea of Islam rahmat li al-ʻalamin brought by Husein Ja'far al-Hadar. This study uses a qualitative approach using descriptive analysis directed at the overall message of da'wah spread on social media: both from Youtube, Twitter, and Instagram. The results of the study show that the idea of ​​Islam rahmat li al-‘alamin Husein Ja'far al-Hadar with a concept based on love emphasizes three important aspects, namely truth, goodness and beauty. Seeing that the times are growing, technology is starting to dominate the world, the existence of Islam must not avoid and be anti-pathy to that reality. So the third option is an Islamic university with the particularization of the times. So in conveying a message must be adapted to the conditions of the times. So that way in today's millennial era, which is better known as the digitalization era, da'wah will be conveyed properly.